3D Virtual Broncoscopy before FETO Procedure in a Fetus with Severe, Isolated Left Congenital Diaphragmatic Hernia. (4th March 2018) - Tonni, Gabriele; Ruano, Rodrigo; Sà, Renato; Peixoto Filho, Fernando Maia; Lopes, Jorge; Werner, Heron
ABSTRACT: Introduction : Congenital diaphragmatic hernia (CDH) is a life-threatening event in severe forms and fetuses affected may benefit from in utero treatment by fetoscopic endotracheal occlusion (FETO). Materials and Methods : Application of 3D virtual bronchoscopy in a case of severe, isolated, left CDH before performing FETO procedure at 27 week's gestation is reported. Results: The 3D virtual imaging of the fetal trachea was technically useful in planning the real FETO procedure. FETO successfully promoted fetal lung growth by decreasing the herniation of abdominal organs into the thorax and decreasing the risk of pulmonary hypoplasia. Ultrasound calculation of lung to head ratio (LHR) and fetal-MRI were used to assess lung development following FETO procedure. Conclusion: 3D virtual fetal reality enabled the fetal surgeon to review and navigate on demand inside the upper airway, reducing the risk of unexpected intervention complications.